2012
DOI: 10.5296/ijhrs.v2i3.2474
|View full text |Cite
|
Sign up to set email alerts
|

Compensation Methods and Employees’ Motivation (With Reference to Employees of National Commercial Bank Riyadh)

Abstract: The main purpose of this research work is to compare the extrinsic and intrinsic rewards which are used as the factors of motivation in the banking sector of Saudi Arabia. With a case study research design, structured interviews were conducted from the eighty (80) employees of NCB seven branched in Riyadh, KSA. The interviews responses were analysed according to Likert technique. After getting scores of ten (10) reward factors, the Pearson correlation technique was calculated to check the relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…Maslow's needs theory (1956) stated that individual needs starts with basic or physiological need, followed by safety, social, esteem needs and self-actualization needs (Aamir et al, 2012). Swinton (2006) explained that esteem needs level employee motivation or satisfaction can be maintained by factors which Herzberg Theory that is called hygiene factors including here salary, benefits and job security (Aamir, et al, 2012).…”
Section: Literature Study Employees' Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Maslow's needs theory (1956) stated that individual needs starts with basic or physiological need, followed by safety, social, esteem needs and self-actualization needs (Aamir et al, 2012). Swinton (2006) explained that esteem needs level employee motivation or satisfaction can be maintained by factors which Herzberg Theory that is called hygiene factors including here salary, benefits and job security (Aamir, et al, 2012).…”
Section: Literature Study Employees' Motivationmentioning
confidence: 99%
“…While motivation is an essential tools for the success of any organization in the long run (Dobre, 2013). Reward positively affect motivation and if designed appropriately, can also boost and support employees for a range of positive outcomes (Patricia Milne, 2007in Aamir et al, 2012. Parvin & Kabir (2011) found that employees' satisfaction can be contributed by good working condition, fairness in job, give promotion and rewards to employees (Yaseen, 2013).…”
Section: Company's Advantagementioning
confidence: 99%
“…Every organization may not have the financial resources to use it as a motivational tool and hence it is important to seek chances and opportunities to acknowledge and value the employees to ensure their retention and higher productivity (Laliberte, Hewitt, Larson, 2003) Allowances: Allowances are considered being a very crucial factor to employee motivation. Many forms of allowances such cash allowance, travel allowance, overtime allowance, and generally individual bonuses are all considered to be an important and significant factor to motivate and retain employees (Aamir et al, 2012). Armstrong (2008) proposed that the difference between allowance and pay is that allowance can be a pay for overtime or maybe adjustment towards increased cost of living, whereas the pay is the rate that could be hourly, monthly, or annually.…”
Section: Rewards and Recognition Motivation And Employee Performancementioning
confidence: 99%
“…Aarabi et al (2013) mentions motivation as the main reason for behaviors. Researchers have different opinions about intrinsic motivation and extrinsic motivation (Aamir et al, 2012). Intrinsic motivation is defined as the activities undertaken to seek satisfaction inherent in a person.…”
Section: Motivationmentioning
confidence: 99%